Comparison of Pre- Pyeloplasty and Post- Pyeloplasty Renal status by 99mTC-DTPA Renogram: A New Experience in a New Institute (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Radionuclide scanning for the functional assessment of kidney is a very helpful procedure. 99mTc DTPA renogram with diuretic challenge can evaluate the improvement or decline of individual renal function and GFR at pre operative and postoperative period in case of pelviureteric junction obstruction (PUJO). Patients and methods: This prospective, longitudinal study was carried out among 25 patients with age ranging from 4 to 57 years at Institute of Nuclear Medicine and Allied Sciences (INMAS), Mohakhali who were referred for the estimation of pre and post pyeloplasty renal status. Results: Mean age of study subjects were 24.54±17.96 years with male predominance (56 %). Left kidney was mostly affected (68%). The pre and post pyeloplasty parenchymal and excretory functions were compared and found to be improved about 56% parenchymal and 64 % in excretory functions respectively. Pre-operative mean glomerular filtration rate (GFR) was 33.49 ± 22.40 ml/min which improved to 44.81 ±25.99 ml / min (33.80%) postoperatively. Conclusion: Comparison of pre pyeloplasty and post pyeloplasty renal status by 99mTc DTPA renogram with diuretic challenge appears to be an authentic and beneficial work up that causes very little radiation exposure to patients but provides important clinical clues for further management and follow up.Bangladesh J. Nuclear Med. 28(1): 105-108, 2025